Social Media in Gay London: Tinder as an Alternative to Hook-Up Apps - MacKee, Freddy (Social media + society, 2016)
The article explores how the mobile app Tinder complements dating practices and the wider app ecosystem gay men use in London. Within the local gay community discourse, Tinder is said to be a site where the gay “nice guys” go, rendering the platform as a socially constructed environment where gay men behave in a diametrically opposed way to the normative hyper-sexualized behavior of widespread gay hook-up apps. The research question, therefore, is whether Tinder is in fact a place where these “nice guys” go and where one would find them. Through an ethnographic methodology conducted both online and offline, a case is built on how initial conceptions about the app cannot be fully studied or interpreted without understanding the place it holds among other social networks. Evidence is presented to support the case that gay users of Tinder do, in fact, curate the portrayal of their digital identity to present a considerably less sexualized persona with the hopes of finding dates or a relationship. This, however, does not mean that users refrain from using other platforms in parallel as a way of exploring different subject positions and motivations. Behavior and normativity on Tinder are largely explained both by context and also by the design of the platform, which imports and displays personal data from other social networks. Findings should be limited to the population and location proposed as the fieldsite.